Pelaksanaan Peran Edukasi Perawat Hemodialisa pada Masa Pandemi Covid-19 - Vivi Retno Intening; Diah Karmini; Kenny Chaiyono; Lidyana Puspitawati; Yulia Friska Ardhiani (FORIKES, 2022)
The impact of the Covid-19 pandemic has also affected patients on routine hemodialysis therapy. This study aims to determine the implementation of the educational role of hemodialysis nurses during the Covid-19 pandemic in 2021. This study uses a qualitative approach. The subjects of this study were hemodialysis nurses who were in the Province of the Special Region of Yogyakarta with a total of six participants. This research stage is in the form of in-depth interviews conducted in August 2021. The data analysis carried out includes transcription, coding, categorization, verification, and triangulation. The results of the study found five themes, namely: 1) the management of education in the hemodialysis room during the pandemic; 2) Educational problems during the Covid-19 pandemic; 3) handling hemodialysis patients after the Covid-19 pandemic; 4) preparation of nurses to carry out education during the Covid-19 pandemic; and 5) nurse support for hemodialysis patients during the Covid-19 pandemic. The conclusion obtained is that the implementation of the educational role of hemodialysis nurses during the Covid-19 pandemic is carried out in various ways. The preparation of nurses in providing education during the Covid-19 pandemic requires modifications, especially in the Standard Operating Procedures (SOP) for the implementation of education during the pandemic.Keywords: Covid-19 pandemic; hemodialysis nurse; educational roleABSTRAK Dampak pandemi Covid-19 juga berimbas pada pasien dengan terapi hemodialisa rutin. Penelitian ini bertujuan untuk mengetahui pelaksanaan peran edukasi perawat hemodialisa pada masa pandemi Covid-19 pada tahun 2021. Penelitian ini menggunakan pendekatan kualitatif. Subjek penelitian ini adalah perawat hemodialisa yang berada di Provinsi Daerah Istimewa Yogyakarta sejumlah enam partisipan. Tahap penelitian ini berupa wawancara mendalam yang dilaksanakan pada bulan Agustus 2021. Analisis data yang dilakukan mencakup transkripsi, koding, kategorisasi, verifikasi, dan triangulasi. Hasil penelitian menemukan lima tema yaitu: 1) penatalaksanaan edukasi di ruang hemodialisa pada masa pandemi; 2) Permasalahan edukasi di masa pandemi Covid-19; 3) penanganan pasien hemodialisa sesudah pandemi Covid-19; 4) persiapan perawat melaksanakan dalam edukasi di masa pandemi Covid-19; dan 5) dukungan perawat pada pasien hemodialisa di masa pandemi Covid-19. Kesimpulan yang didapatkan adalah bahwa pelaksanaan peran edukasi perawat hemodialisa di masa pandemi Covid-19 dilakukan dengan berbagai cara. Persiapan perawat dalam memberikan edukasi pada masa pandemi Covid-19 memerlukan modifikasi, terutama pada Standar Operasional Prosedur (SOP) pelaksanaan edukasi di masa pandemi.Kata kunci: pandemi Covid-19; perawat hemodialisa; peran edukasi